2001
DOI: 10.1046/j.1360-0443.2001.96227311.x
|View full text |Cite
|
Sign up to set email alerts
|

Revising the preventive paradox: the Swiss case

Abstract: As Skog has pointed out, the second-order preventive paradox of binge drinking reappeared, in that most binge drinkers were found to occur in the drinker group with low average consumption. Findings also indicate that, with respect to social harm, a preventive strategy aimed at the majority of the population, but on heavy-drinking occasions rather than on mean consumption, may be valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
84
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 0 publications
20
84
0
Order By: Relevance
“…When they defi ned high-risk using per occasion thresholds, 87% of those 67 individuals reported hazardous drinking on the day the event occurred. Gmel et al 7 and even Kreitman 5 reported similar fi ndings. Assessment of per-occasion alcohol consumption, however, has been limited.…”
Section: Introductionmentioning
confidence: 71%
“…When they defi ned high-risk using per occasion thresholds, 87% of those 67 individuals reported hazardous drinking on the day the event occurred. Gmel et al 7 and even Kreitman 5 reported similar fi ndings. Assessment of per-occasion alcohol consumption, however, has been limited.…”
Section: Introductionmentioning
confidence: 71%
“…It is observed when a large number of people at small risk contribute more cases of a disease or negative health outcome in a population than do a small number of people at large risk. Researchers in the United States and internationally have demonstrated the importance of this perspective for alcohol using large representative data sets for a variety of negative alcohol related outcomes [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is showed, too, that the probabilities of being a victim of predatory crime for females who are weekly or more frequent drinkers are higher than those for males, which could reflect the fact that females, especially those who drink frequently, are more likely to be victims of various crimes [22]. Analyses have shown that the majority of problems may occur in relation to heavy drinking occasions, and that the number of people with heavy drinking occasions is larger among low-moderate consumers than among heavy consumers [28,29,30,144].…”
Section: Discussionmentioning
confidence: 99%